ESTIMATION OF MOST PROBABLE PRODUCING ABILITY VALUE FOR CALF BIRTH'S PERFORMANCE IN SUMBA ONGOLE COWS - Said, S.; Agung, P. P.; Putra, W. P. B.; Anwar, S.; Wulandari, A. S.; Sudiro, A. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
An estimation of most probable producing ability (MPPA) value based on the calves performance is very important for the cow selection. The birth data record of 48 Sumba Ongole (SO) cows and record data from 52 callf birth’s performance were used to estimate the value of MPPA. High of r value (r > 0.30) was obtained at the body length (BL). Birth weight (BW), withers high (WH) and chest girth (CG) had a moderate value (0.10 < r < 0.30) of repeatability. The MPPA value of the cumulative calf birth’s performance of cows based on the highest birth records was 4.64 (cow number 3770) and the lowest was -4.64 (cow number 2283). Calf number B2076 (cow number 3586) had the highest ratio of WH (115.70); BL (124.26); CG (118.90), while the highest ratio of BW (168.35) was obtained in calf number B2095 (cow number 3731). It was concluded that the BW of birth had a moderate value of r (0.10) and could be used as a selection criteria accurately.